Controlling Legionella pneumophila growth in hot water systems by reducing dissolved oxygen levels. - Krause, J. David (Journal of Occupational & Environmental Hygiene, 2024)
Legionella pneumophila, the leading cause of Legionnaires' disease in the United States, is found in lakes, ponds, and streams but poses a health risk when it grows in building water systems. The growth of L. pneumophila in hot water systems of healthcare facilities poses a significant risk to patients, staff, and visitors. Hospitals and long-term care facilities account for 76% of reported Legionnaires' disease cases with mortality rates of 25%. Controlling L. pneumophila growth in hot water systems serving healthcare and hospitality buildings is currently achieved primarily by adding oxidizing chemical disinfectants. Chemical oxidants generate disinfection byproducts and can accelerate corrosion of premise plumbing materials and equipment. Alternative control methods that do not generate hazardous disinfection byproducts or accelerate corrosion are needed. L. pneumophila is an obligate aerobe that cannot sustain cellular respiration, amplify, or remain culturable when dissolved oxygen (DO) concentrations are too low (< 0.3 mg/L). An alternative method of controlling L. pneumophila growth by reducing DO levels in a hot water model system using a gas transfer membrane contactor was evaluated. A hot water model system was constructed and inoculated with L. pneumophila at DO concentrations above 0.5 mg/L. Once the model system was colonized, DO levels were incrementally reduced. Water samples were collected each week to evaluate the effect of reducing dissolved oxygen levels when all other conditions favored Legionella amplification. At DO concentrations below 0.3 mg/L, L. pneumophila concentrations were reduced by 1-log over 7 days. Under conditions in the hot water model system, at favorable temperatures and with no residual chlorine disinfectant, L. pneumophila concentrations were reduced by 1-log, indicating growth inhibition by reducing DO levels as the sole control measure. In sections of the model system where DO levels were not lowered L. pneumophila continued to grow. Reducing dissolved oxygen levels in hot water systems of healthcare and other large buildings to control L. pneumophila could also lower the risk of supplemental chemical treatment methods currently in use.